TECHNOLOGIES OF TEACHING ABDULLAH QADIR'S CREATIVITY IN EDUCATION - Karimova Muxtabar Adhamovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the theoretical basis for introducing the works of literary critics, writers and poets to students in the education system. It also describes the techniques used to introduce Abdullah Qadiri's life and career.